PENGARUH SUBSTITUSI ION Ti-Zn TERHADAP SIFAT KEMAGNETAN dan SIFAT PENYERAPAN GELOMBANG ELEKTROMAGNETIK MATERIAL SISTEM BaFe12-xTix/2Znx/2O19 - Nenni Nenni; Mutia Delina; Wisnu Ari Adi; Yana Taryana (Program Studi Fisika Universitas Negeri Jakarta, 2017)
Substitution of Ti+4 and Zn+2 ions on magnetic material BaFe12-xTix/2Znx/2O19 (x = 0 and 2) using the wet milling method has been performed. This research was conducted to get information the influence of Ti-Zn substitution on magnetic properties and its absorption. The magnetic material BaFe12-xTix/2Znx/2O19 is synthesized from a mixture of oxide materials, BaCO3, Fe2O3, TiO2 and ZnO. The mixture was milled for 5 hours, dried at 1000C then sintered at 10000C for 5 hours. The refinement result of the X-ray diffraction pattern shows that the sample has single phase BaFe12O19 with doping concentration of x = 0 and 2. The hysteresis curve shows that coercivity field value decreased in the sample with doping concentration of x = 2. The result of electromagnetic wave absorption shows that the substituted sample with Ti+4 and Zn+2 ions (doping concentration x = 2) has the highest absorption peak at a frequency of 11,2 GHz with reflection loss value (RL) of -24,3 dB. Electromagnetic wave absorption reaches 94% with sample thickness is about 1,0 mm. Therefore, the magnetic material BaFe12-xTix/2Znx/2O19 (x = 2) can be used for application of the electromagnetic wave absorber. Keywords: Substitution, BaFe12-xTix/2Znx/2O19, wet milling, reflection loss, electromagnetic wave absorber.